2017
DOI: 10.4012/dmj.2016-225
|View full text |Cite
|
Sign up to set email alerts
|

Retention and caries-preventive effect of glass ionomer and resin-based sealants: An 18-month-randomized clinical trial

Abstract: The objective of this study was to compare the retention and caries-preventive effect of glass ionomer (Fuji Triage) and resin-based (Clinpro) sealants among 6-9-year-old children. This split-mouth, randomized clinical trial covered 35 children/140 fully erupted permanent first molars. Evaluation was conducted by two independent examiners after 6, 12, and 18 months and the data were compared in relation to the children's caries risk and age groups. The Kaplan-Meier survival method and chi-square test were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The experimental RBS tested in this study interacted adequately with both sound and demineralized enamel. This latter situation may be related to the adhesion of resin-based sealants, the longevity of the treatment 5,9,28 and the extent of the preventive effect. It is well known that high-viscosity resin-based materials may be less able to penetrate into occlusal pits and fissures 29 and this may affect the micromechanical interaction between the tooth and the resin sealant interface 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental RBS tested in this study interacted adequately with both sound and demineralized enamel. This latter situation may be related to the adhesion of resin-based sealants, the longevity of the treatment 5,9,28 and the extent of the preventive effect. It is well known that high-viscosity resin-based materials may be less able to penetrate into occlusal pits and fissures 29 and this may affect the micromechanical interaction between the tooth and the resin sealant interface 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, pits and fissures sealing offers reliable protection against caries, which reduces the incidence of such a disease up to 18,92% in permanent molars in 5 to 10 years old children 3 . The effectiveness of resin-based sealants is well established 4,5 as a cost-effective treatment for controlling caries lesions 57 .…”
Section: Introductionmentioning
confidence: 99%
“…Polyacid modified resin sealants also showed low retention rates [ 46 ]. However, studies that used HVGIC [ 50 , 51 ] or Fuji Triage [ 52 ] have shown improved retention rate results for GI sealants that are comparable to resin-based sealants.…”
Section: Sealant Retention Of Different Materialsmentioning
confidence: 99%
“…However, prevention with oral hygiene and fluoridated treatments is not totally efficient in preventing disease in pits and fissures when compared to smooth surfaces [5]. Therefore, the introduction of preventive measures that minimize the onset and progression of caries disease, especially in school children is necessary, since they have permanent molars in the stage of eruption [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The transversal brushing technique, specifically directed to these teeth, is effective in controlling the local biofilm and at the same time contributes to the maintenance of small amounts of fluoride in the oral environment [13,15]. In addition, sealing of pits and fissures has been shown to be highly effective with regard to the prevention of caries lesions [7,13]. Although studies have shown resinous materials as the material of choice, there are still gaps in showing the best evidence to put into clinical practice [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%